Problematika Dakwah Lembaga Pendidikan dan Dakwah Addakwah Sumatera Utara dalam Meningkatkan Ibadah Shalat Berjamaah di Daerah Minoritas Muslim Desa Penampen Kecamatan Tiganderket Kabupaten Karo - Siregar, Monica Tri Weni (MASALIQ, 2023)
This study aims to determine the problems faced by the Addakwah Institute of North Sumatra in increasing congregational prayer services in Muslim minority areas, especially in Penampen Village, Tiganderket District, Karo Regency. This study uses a qualitative method with a type of field research. This study uses data collection techniques by means of interviews, observation, and documentation. The informants in this study were the Director of the North Sumatra Addakwah Institute, the dai of the North Sumatra Addakwah Institute who preached in the area, and the people of Penampen Village. The results of the research conducted in this study show: first, the implementation of da'wah by the Addakwah Institute of North Sumatra is very good, especially in terms of socializing with the community to gain the trust of the community because their trust is an important part of a relationship. After a relationship is created, the preachers will invite the public to pray in congregation at the mosque. In the implementation of da'wah each of the elements of da'wah has its own role, namely competent preachers, mad'u who are the objects of da'wah, effective methods, materials that are in accordance with needs, and media that assist in the spread of da'wah. Second, in carrying out da'wah there are several problems, the biggest problems of da'wah come from the community itself because they have different backgrounds and also the community does not fully accept the da'wah that is being carried out. Limited methods and media are also a problem in this regard. The preachers also have low self-confidence in carrying out their da'wah. The three solutions that Dai can use are preaching from house to house and providing understanding to the public about Islamic teachings and utilizing methods and media by relying on technology that can be used even if they don't have an internet network. At the same time increasing self-confidence in the da'i itself.